2015
DOI: 10.21859/isv.9.2.20
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Survey on Antibodies against Akabane Virus in Sheep in Southwest of Iran

Abstract: Background and Aims: Akabane disease causes epidemics of abortions, stillbirths and congenital malformations manifested as arthrogryposis and hydranencephaly or microanencephaly in sheep, goats and cattle. Akabane virus replicates in arthropods and is transmitted by either mosquitoes or midges. Outbreaks of the Akabane virus have been reported from many countries in Southeast Asia, Middle East, Africa and Australia. The aim of this study was to evaluate the prevalence of Akabane virus infection and correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
3
13
1
Order By: Relevance
“…The present study showed that the odds of infection was increased with increase of age. This result confirmed reports of Oluwayelu et al (2016) and Elhassan et al (2014), who reported a significant difference but didn't confirm recently records of Ahi et al (2015). Whereas infection in adult cattle is common in endemic areas, reports of clinical disease are rare but neurological disease associated with infection in cattle 2 to 7 years of age has been observed (29).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The present study showed that the odds of infection was increased with increase of age. This result confirmed reports of Oluwayelu et al (2016) and Elhassan et al (2014), who reported a significant difference but didn't confirm recently records of Ahi et al (2015). Whereas infection in adult cattle is common in endemic areas, reports of clinical disease are rare but neurological disease associated with infection in cattle 2 to 7 years of age has been observed (29).…”
Section: Discussionsupporting
confidence: 57%
“…The present study revealed that prevalence rates were associated with sex. This result confirmed reports of Elhassan et al in 2014 but didn't confirm recently records of Ahi et al (2015) and Oluwayelu et al (2016). There is no sex predilection for this virus and affects both sex.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Akabane virus infection is distributed in Middle Eastern countries such as Cyprus, Iran (Ahi et al, 2015), Israel (Stram et al, 2004), Saudi Arabia (Abu Elzein et al, 1998), Jordan, Syrian Arab Republic and Turkey (Taylor & Mellor, 1994). Geographically, Iraq is bordered by a vast area of these endemic countries such as Iran, Jordan, Saudi Arabia, Syrian Arab Republic, and Turkey.…”
Section: Discussionmentioning
confidence: 99%